1970
DOI: 10.1039/tf9706601932
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red cryogenic studies. Part 5.—Ethanol and ethanol-d argon matrices

Abstract: Infra-red spectra between 4000 and 40cm-I are reported for EtOH and EtOD suspended in argon matrices at 20 K. The small bandwidths in the low-temperature matrix reveal the presence of bands due to both trans and gauche conformers, and a complete vibrational assignment for the more stable trans conformer is made. The ratio of trans to gauche conformers in the vapour phase at room temperature is estimated to be 2 : 1. Concentration studies result in the identification of open chain dimer, trimer and tetramer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 0 publications
9
85
1
Order By: Relevance
“…23 The far-infrared absorption spectrum of ethanol embedded in cryogenic argon matrices has previously just revealed two strong transitions observed at 211 and 264 cm −1 besides the strong CCO bending fundamental transition at 416.5 cm −1 . 20 In the present far-infrared spectra of ethanol embedded in more inert cryogenic neon matrices, a series of weak, medium-intensity, and strong bands are observed besides the strong CCO bending fundamental transition at 419.9 cm −1 (Fig. 1).…”
Section: Vibrational Assignments For the Mixed Ethanol/water Commentioning
confidence: 51%
“…23 The far-infrared absorption spectrum of ethanol embedded in cryogenic argon matrices has previously just revealed two strong transitions observed at 211 and 264 cm −1 besides the strong CCO bending fundamental transition at 416.5 cm −1 . 20 In the present far-infrared spectra of ethanol embedded in more inert cryogenic neon matrices, a series of weak, medium-intensity, and strong bands are observed besides the strong CCO bending fundamental transition at 419.9 cm −1 (Fig. 1).…”
Section: Vibrational Assignments For the Mixed Ethanol/water Commentioning
confidence: 51%
“…The band at 3014 cm-' in I (3006 cm-' in 11) is assigned to the antisymmetric v,(CHd mode, and the band at 2895 cm-' in I(2899 cm-I in 11) to the symmetric v,(CH,) mode. In the case of ethanol, the antisymmetric and symmetric CH, stretching modes of the hydroxyniethyl group are observed at 2953 cm-' and at 2900 cm-' , respectively (29).…”
Section: The Ch Stretching Regionmentioning
confidence: 95%
“…Several matrix-isolation infrared selfdence of the monomer hydroxyl stretching band only, association studies have shown that hydrogen while the band due to association or complex forma-bonding manifests itself in all three vibrational tion was usually ignored. The application of factor modes of the hydroxyl group in alcohols (6,7). When analysis (principal component analysis) to digitized complex formation occurs between alcohols or infrared spectra leads to the determination of the phenols and ketones, both the v(0H) band and the number of absorbing components in a complex band v(C0) band show concentration dependencies (4).…”
Section: Tntpoductionmentioning
confidence: 99%
“…[6] instead of the monomeric acceptor concent3aiion. For comparison, P : l equilibriunl constants were also calculated using the areas of the monomer ~ ( 0 1 4 ) band.…”
Section: Chen?icnl Equilibritrn~mentioning
confidence: 99%